Mechanisms of climate-induced lake dynamics in the Source Region of Three Rivers, Tibetan Plateau - Xiankun Zheng; Sihai Liang; Dezhao Yan; Xingxing Kuang; Li Wan (Journal of Hydrology: Regional Studies)
Study region: The Source Region of the Three Rivers (SRTR), Tibetan Plateau, China. Study focus: Lake variation studies in the SRTR have primarily focused on a few large lakes, with limited understanding of the long-term trends, stages, and main driving mechanisms of change in lakes larger than 1 km², especially the role of groundwater. This study proposes an attributing framework based on trend tests and water balance to investigate the changes in SRTR lakes with areas over 1 km² from 1990 to 2019. Nearly all potential drivers of lake dynamics, including groundwater, precipitation, evapotranspiration, glaciers, permafrost, and geological structure, are incorporated into the analysis. New hydrological insights for the region: Results indicate an upward trend in the number of lakes (approximately 29 %), area (around 17 %), and volume (growing at an estimated 0.23 Gt/yr). Trend tests and water balance methods revealed that changes in groundwater significantly impacted 47 lakes (including 18 endorheic and 7 exorheic basins). Incorporating precipitation, evapotranspiration, and other factors, we further classified these changes into eight expansion patterns (involving 198 lakes) and four shrinkage patterns (involving 4 lakes), highlighting the diverse response mechanisms of lakes. Additionally, a three-phase evolutionary trend in the spatiotemporal dynamics of lakes was identified, providing a scientific basis for precise water resource regulation and lake ecosystem protection under different future scenarios in the SRTR.